Предмет: Алгебра, автор: kola3tselinko

Помогите даю 60 балов​

Приложения:

Ответы

Автор ответа: сок111213
0

 - 3 {x}^{2}  - x + 2 > 0 \\ 3 {x}^{2}  + x - 2  < 0 \\  \\ 3 {x}^{2}  + x - 2 = 0 \\ a =  3\\ b = 1 \\ c =  - 2 \\ D =  {b}^{2}  - 4ac =  1 {}^{2} - 4 \times 3 \times ( - 2) =  1+ 24 = 25 \\ x_{1} =  \frac{ - 1 - 5}{2 \times 3}  =  -  \frac{6}{6} =  - 1  \\ x_{2} =  \frac{ - 1 + 5}{2 \times 3}  =  \frac{4}{6}  =  \frac{2}{3}  \\  \\  {ax}^{2}  + bx + c = a(x - x_{1})(x - x_{2}) \\ 3 {x}^{2}  + x - 2 = 3(x  + 1)(x -  \frac{2}{3} ) \\  \\ (x + 1)(x -  \frac{2}{3} ) < 0 \\  +  +  + ( - 1) -  -  - ( \frac{2}{3} ) +  +  +  \\ x \:\epsilon  \: ( - 1; \:  \frac{2}{3} )

Ответ: 0

Похожие вопросы
Предмет: Алгебра, автор: kazaly66
Предмет: Математика, автор: moscosojosefia